(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
In this article, Sinc collocation method is considered to obtain the numerical solution of integral algebraic equation of index-1 by reducing it to an explicit system of algebraic equation. It is shown that Sinc collocation solution can produce an error of order O(√Ne^−k√N). Moreover, Sinc method is applied to several examples to illustrate the accuracy and implementation of the method.